(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: According to WHO, obesity or overweight are risk factors of psychological disorders and quality of life deterioration. Objective: Evaluating the impact of overweight on body image and self-esteem in a population of Moroccan adolescents and adults. Method: The study was carried out on 288 subjects (150 men, and 138 women), aged on average 34,86±0,82 years [15 -76]. Over weight was measure dusing the Body Mass Index (BMI), body image was evaluated using the Physical Appearance Comparison Scale (PACS), and self-esteem was evaluated using the Rosenberg Self-Esteem Scale (RSES). Results: 43,28 % (n= 103) of subjects had a normal body weight, 25,63% (n=61) were overweight and 16,81% (n=40) were obese. 66,67% (68/102) of over weight subjects reported having compared their physical appearance to others. However, 60,46 % (78/129) of thosewith normal BMI also reported having compared their appearance to others some times or often. Among obese subjects, 73,68% (42/57) tend to compare their physical appearance to others some times or often. In terms of self-esteem, 85,3% (n=209) have a low to verylow self-esteem, 13,1% (n=32) have a moderate self-esteem and 1.6% have a high selfesteem. However, only 15,13% (28/185) of subjects with normal BMI had a moderate to high self-esteem. A negative correlation was found between PACS and RSES (r= -0,139) and statistically significant correlations were found between BMI and both PACS (r= +0.125) and RSES (r= -0.189). Conclusion: Consequently, it is recommended to establish multi-disciplinary programs for management of over weight among adolescents and adults, to mainstream the care received and reduce the pressure they experience.